DEVELOPMENT OF MATHEMATICAL LEARNING DEVICES BASED ON PROBLEM BASED LEARNING MODEL ON THREE DIMENSIONAL MATERIAL TO FACILITATE HIGHER-ORDER THINKING SKILLS FOR STUDENTS IN CLASS XII SMA/MA - Nur Samsi; Sehatta Saragih; Rini Dian Anggraini (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This research produces a product in the form of a mathematics learning device using a Problem Based Learning model on Three Dimensional material to facilitate students' Higher Order Thinking Ability. Validity and practicality is the instrument of the research. 4-D is a model of development. The validity instrument is in the form of a validation sheet to assess the validity of the learning tools, namely the syllabus, RPP, and LAS. The practicum instrument is a student response questionnaire to assess the usefulness and ease of use of LAS. Three validators will validate it and revise it according to the validator's suggestions. Then a limited group trial was conducted with six students. The results of syllabus validation 3.79, RPP 3.73, and LAS 3.58 are very valid. While the result of LAS is 85.15%, it is said to be a very practical category. Based on these, it was concluded that this study produced a product in the form of a mathematical learning device based on the Problem Based Learning model on Three Dimensional material that was valid for syllabus, RPP, and LAS and practical for LAS.